Estonia as a Sign. - Borgs, Janis; Juske, Ants; Kelomees, Raivo; Kodres, Krista; Krull, Hasso; Kurvitz, Raoul; Küttner, Urve; Laimre, Marko; Linnap, Peeter; Luik, Airi; Pustak, Kaisa; Põder, Anu; et al. (Tallinn : Soros Center for Contemporary Arts, 1996)
Josing, Inessa ; Kangilaski, Kadri ; Kuusing, Kai ; Küttner, Urve ; KYNA (Silver Vahtre & Tõnu Noorits) ; Laidro, Kalev ; Laimre, Marko ; Lapin, Leonhard ; Laurentsius ; Linnap, Peeter ; Meel, Raul ; Mäetamm, Marko ; Nukke, Mall ; Remme, Annelli ; Riitsaar, Evar ; Rani, Piret ; Semper, Ene-Liis ; Siib, Liina ; Tonts, Annika ; Tralla, Mare ; Viljus, Mart ; Prääts, Rait ; Ojaver, Terje ; Pustak, Kaisa ; Remme, Rauno ; Linnap, Eve ; Mauni, N. ; Põder, Anu ; Josing, Inessa ; Juurak, Anu ; Luik, Airi ; Ojaver, Jüri ; Saks, Jaak ; Tonts, Annika ; Kelomees, Raivo ; Kruusamäe, Ilmar ; Elken, Jaan ; Johannson, Tiia ; Kaljuste, Mari ; Kurismaa, Mari ; Kõresaar, Andrus ; Luik-Mudist, Ene ; Kask, Margot ; Kurvitz, Raoul ; Nagel, Lemming ; Smidt, Tõnu
biog., ind. tent., gr. tent., prijzen [22 p.]
Engels & Ests
Estonia as a sign, 4th Annual Exhibition of the Soros Center for Contemporary Arts, Estonia, Tallinn, 26. september - 13. oktober 1996, Tallinn Art Hall, Tallinn ; Gallerii Sammas, Tallinn ; Vaal Galerii, Tallinn ; Tartu Kunstnike Maja, Tallinn ; Rüütli Gallerii, Tallinn
kunstcatalogus
Keywords: Estland